The meaning of the Pentateuch: revelation, composition, and interpretation - Sailhamer, John H. (IVP Academic, 2009)
Introduction -- Approaching the text as revelation -- Understanding the nature and goal of Old Testament theology -- Finding the author's verbal meaning -- What is the historical meaning of biblical texts? -- Finding the big idea in the final composition of the text -- Rediscovering the composition of the Pentateuch within the Tanak -- Textual strategies within the Tanak -- The composition of the Pentateuch -- Textual strata and strategy in the Pentateuch -- Interpreting the theology of the Pentateuch -- The nature of covenant and blessing in the Pentateuch -- Is there a biblical Jesus in the Pentateuch